Detecting Renibacterium salmoninarum in cultured and wild salmonids - Ívar Örn Árnason 1982- (2010)
Renibacterium salmoninarum, that causes bacterial kidney disease (BKD), is endemic in both wild and farmed stocks of salmonids worldwide, including Iceland. The disease is mainly a problem in culture, in fresh and marine water, although epidemics and clinical signs of BKD are observed in wild fish. Therapeutic measures, including the use of antibiotics or vaccines, have been tried with limited success. Brood stock culling, where fertilized ova from infected females are destroyed, is an important method in the battle against the disease and therefore rapid diagnostic tests are important. The diagnostic methods currently used for screening are Fluorescent antibody techniques (FAT), enzyme-linked immunosorbent assays (ELISA) and polymerase chain reactions (PCR) and for these analyses, kidney tissue is most commonly used. Culture is used in diagnostics, but the slow growth of the bacterium hampers the use of culture for screening purposes. The main objectives of the study were to develop a cheap, specific and sensitive PCR method to use along with an ELISA test for screening as well as confirmative purposes. Also, to compare such a method with other PCR tests, esp. the nested PCR (nPCR) test recommended by OIE, the World Organization of Animal Health. The use of FTA minicard, an easy way to isolate and store DNA, was also tested and compared to conventional method. The protocols were tested in cultured salmon with active infection and in wild Atlantic salmon, Arctic charr and brown trout from Lake Ellidavatn and River Ellidaár that flows from the lake. To investigate how long bacterial antigens can be detected in salmonid kidney after exposure to extracellular products (ECP) of the bacterium, Atlantic salmon fry from a BKD free farm were injected intra-peritoneally with two different doses of ECP and sampled over 6 weeks. A semi-nested PCR (snPCR) method was developed in the study and proved to be as sensitive as nPCR. These two methods detected more positive samples than other PCR methods tested. Using FTA minicard ...